5, 11‐Diazadibenzo[hi, qr]tetracene: Synthesis, Properties, and Reactivity toward Nucleophilic Reagents. Issue 35 (17th May 2021) - Fujimoto, Keisuke; Takimoto, Satoshi; Masuda, Shota; Inuzuka, Toshiyasu; Sanada, Kazutaka; Sakamoto, Masami; Takahashi, Masaki
Abstract: 5, 11‐Diazadibenzo[ hi, qr ]tetracene was synthesized as a new nitrogen‐substituted polycyclic heteroaromatic compound by Pd‐catalyzed cycloisomerization of an alkyne precursor followed by oxidative cyclization with bis(trifluoroacetoxy)iodobenzene. The substitution of imine‐type nitrogen atoms significantly enhanced its electron‐accepting character and facilitated the direct nucleophilic addition of arylamines under strongly basic conditions to afford the desired amino‐substituted products. The introduction of amino groups induced a remarkable red‐shift in their absorption spectra; the tetrasubstituted product exhibited intense near‐infrared absorbing property. Furthermore, the π‐electronic system, which includes a redox‐active 1, 4‐diazabutadiene moiety, underwent reversible interconversion to its corresponding reduced form upon reduction with NaBH4 and aerobic oxidation. Abstract : New n‐type material ? 5, 11‐Diazadibenzo[ hi, qr ]tetracene was synthesized as a new nitrogen‐substituted polycyclic heteroaromatic molecule. This compound showed enhanced electron‐accepting character and specific reactivities toward nucleophilic reagents. Reaction with arylamines provided an aminated product that shows an intensely NIR‐absorbing character. Furthermore, a reversible interconversion into the corresponding reduced form was realized.